2016
DOI: 10.15283/ijsc.2016.9.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid-Derived Mesenchymal Stem Cells Cut Short the Acuteness of Cisplatin-Induced Nephrotoxicity in Sprague-Dawley Rats

Abstract: Background and objectivesCisplatin is a nephrotoxic chemotherapeutic agent. So, preventive measures worth to be evaluated. Human amniotic fluid stem cells (hAFSCs) in prevention or amelioration of cisplatin-induced acute kidney injury (AKI) in Sprague-Dawley rates have been tested.Methods80 Sprague-Dawley rats (250~300 g) were used and divided into 4 major groups, 20 rats each. Group I: Saline-injected group. Group II: Cisplatin-injected group (5 mg/kg I.P). Group III: Cisplatin-injected and hAFSCs-treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In xenogeneic studies, good results in terms of survival rate, renal function and morphology were achieved through the application of different types of hMSC, such as hBM-MSC ( 195 , 196 ), hAFSC ( 182 , 192 ), hESC-MP ( 190 ), hUC-MSC ( 32 , 179 , 187 , 189 ), hUCB-MSC ( 31 , 85 ). Recently, hASC have become the most widely used cell type in animal experiments, resulting in good treatment results in AKI ( 180 , 183 , 184 , 186 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 99%
“…In xenogeneic studies, good results in terms of survival rate, renal function and morphology were achieved through the application of different types of hMSC, such as hBM-MSC ( 195 , 196 ), hAFSC ( 182 , 192 ), hESC-MP ( 190 ), hUC-MSC ( 32 , 179 , 187 , 189 ), hUCB-MSC ( 31 , 85 ). Recently, hASC have become the most widely used cell type in animal experiments, resulting in good treatment results in AKI ( 180 , 183 , 184 , 186 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 99%
“…Cells at passages 3–5 were trypsinized with 0.25% trypsin–EDTA solution, washed with phosphate-buffered saline (PBS), counted and incubated at room temperature for 30 min in the dark, with monoclonal phycoerythrin (PE)-conjugated antibody for CD45 (Abcam, ab23396, UK), monoclonal fluorescein isothiocyanate (FITC)-conjugated antibody for CD90 (Anti-Thy1.1) (Abcam, ab225, UK), and the monoclonal FITC-conjugated antibody for OCT4 antibody (Abcam, ab181557, UK). Immunofluorescence on the viable cells was analyzed using Becton Dickinson, FACS caliber flow cytometer equipped with Cell Quest software [ 12 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…AFSC seem to protect tubular and glomerular cells by stimulating endogenous repair mechanisms, thus reducing inflammation and fibrosis . Other groups showed that these cells enhance recovery in 5/6 Nx models and cisplatin‐induced toxicity .…”
Section: Different Types Of Stem Cells and Preclinical Models Of Renamentioning
confidence: 99%